The Impact of TQM on Sustainable Competitive Performance: A Mediating Role of Organizational Flexibility - Sharayah, Qusay Mikhled; Tarawneh, Heba Akram; Sharayah, Oday Mikhled (Journal of Ecohumanism, 2025)
The study aims to understand how quality management practices can enhance sustainable competitiveness, and how organizational flexibility can enhance this impact in Jordanian telecommunications companies. In this study, a quantitative research approach was employed. The study population consists of administrative and operational employees working in the telecommunications sector in Jordan, a representative sample of 355 respondents. To evaluate the collected data, the study utilized SmartPLS-4. The findings indicate that organizational flexibility mediates the relationship between TQM and sustainable competitive performance. This means that TQM initiatives improve flexibility thus improving competitive performance. Based on the study Organization must not only pay attention to TQM practices, but should also strive to incorporate flexibility into the organization. In order to take full advantage of these findings, several recommendations are possible. The results show that organizations in the telecommunications sector should particularly focus on training initiatives that prepare the workers in TQM Tenets & Techniques respectively. Such training can certainly improve service delivery and quality as well as the organizations’ commitment to improving quality system wide. However, continuous improvement and creation of a culture that supports it would need to be developed. Promoting such a culture through feedback mechanisms and employee participation in decision making can further this practice optimize TQM as well as incorporate greater flexibility into the organization. Another internal factor that companies should consider is work flexibility.